Residual brain injury after early discontinuation of cooling therapy in mild neonatal encephalopathy. Issue 4 (21st September 2017) - Lally, Peter J; Montaldo, Paolo; Oliveira, Vânia; Swamy, Ravi Shankar; Soe, Aung; Shankaran, Seetha; Thayyil, Sudhin
Abstract : We examined the brain injury and neurodevelopmental outcomes in a prospective cohort of 10 babies with mild encephalopathy who had early cessation of cooling therapy. All babies had MRI and spectroscopy within 2 weeks after birth and neurodevelopmental assessment at 2 years. Cooling was prematurely discontinued at a median age of 9 hours (IQR 5–13) due to rapid clinical improvement. Five (50%) had injury on MRI or spectroscopy, and two (20%) had an abnormal neurodevelopmental outcome at 2 years. Premature cessation of cooling therapy in babies with mild neonatal encephalopathy does not exclude residual brain injury and adverse long-term neurodevelopmental outcomes. This study refers to babies recruited into the MARBLE study (NCT01309711, pre-results stage).